OUTCOME OF THERAPEUTIC KERATOPLASTY IN NON-HEALING CORNEAL ULCER: A RETROSPECTIVE STUDY. - Padhy, Sujata Padhy; Mahapatro, Sanjukta; Sabita , Devi; Dash, Suchitra (Student's Journal of Health Research Africa, 2023)
Background: In developing nations like India, corneal blindness has been a major cause of visual impairment. Primarily, corneal ulcer is the primary cause of monocular blindness. Considering the prevalence of the condition, there have been surprisingly few studies and publications on corneal ulcers and their management. With the introduction of therapeutic penetrating keratoplasty (TPK), however, the incidence and prevalence of corneal blindness can be diminished. In order to determine the significance of therapeutic penetrating keratoplasty in cases of non-healing infected and perforated corneal ulcers, this study was conducted. Aim: The objectives were to evaluate the clinical outcome of a perforated and non-healing corneal ulcer, the reduction of symptoms and indicators of infection, the anatomical or structural integrity of the globe, and the visual outcome of therapeutic penetrating keratoplasty. Methods: Data were obtained from 74 patients who underwent therapeutic penetrating keratoplasty at our institution. Patients with a follow-up period of less than one-year, paediatric cases, and PL-negative cases were excluded. The outcome was evaluated based on the maintenance of structural integrity, reduction in infectious burden, improvement in visual acuity, and graft survival, as well as its correlation with corneal vascularisation, previously failed grafts, donor tissue quality, graft size, and surgery type. Results: From a total of 74 cases, 47 (63.51%) were male. The majority of the patients were farm labourers. In our study, refractory corneal ulcer treated with Hypopion was the most prevalent indication for TPK. Conclusion: In the case of non-healing and perforated corneal ulcers, the study demonstrated that therapeutic penetrating keratoplasty has a favorable prognosis for reducing the infectious burden and maintaining structural integrity, without which the eye could have been lost.